STRATEGI DUA-DUA-EMPAT UNTUK MENINGKATKAN KETERAMPILAN KEPEWARAAN MAHASISWA - Pristiwati, Rahayu (Universitas Negeri Semarang, 2012)
The purpose of this research is to improve the quality of the lecture that is designed based on the strategy two-two-four students in the kepewaraan lecturing on kepewaraan course participants, and also to describe the amount of increase in the quality of students learning outcomes after attending kepewaraan strategy with two-two-four and uncover students’s responses as feedback learning outcomes assessment designed to reveal the strategy performance in two-twofour can provide significant feedback to the positive response of students. the subject of the study were students of Education Studies Language and Literature Indonesia. Learning strategy implemented using two journals and document images. Processes and students learning outcomes were analyzed with qualitative and quantitative techniques. the results showed the process, learning outcomes, and students responses can be enhanced through the application of strategy of two-two-four, arranged in twelve steps.